Konflikt wokół odbudowy świątyni (Ezd 4,1-5). Przyczynek do transformacji religii biblijnego Izraela i narodzin judaizmu - Chrostowski, Waldemar (Collectanea Theologica, 2019)
This article presents the detailed exegesis of the text of Esd 4,1-5. First, the place of this text in the structure of the Book of Esdra is described and the translation into Polish is given. Then, detailed remarks follow regarding all the verses included. Verse 1 gives the identity of the delegation coming to Jerusalem as seen by the author of the Book of Esdra. Verse 2 preserves the self-presentation of the delegates from the north, and the article stresses the fact that they were believers in YHWH. The answer given in v. 3 by the Jerusalem authorities is analysed in detail. Verses 4-5 describe the conflict with “the people of the land”, in many respects having analogies with similar antagonisms between Jerusalem and Judah and the population of the former Kingdom of Israel. By the end of the article some important conclusions are proposed, among them the question as to whether the Jerusalem authorities would accept the proposal of collaboration in the cult existing in Jerusalem presented immediately after 539 by the delegates coming from the north. The crucial question regards the long-lasting and still valid issue of the identity of the “true Israel”.